Performance evaluation of digital pulse position modulation for wavelength division multiplexing FSO systems impaired by interchannel crosstalk - Mbah, Afamefuna Maduka; Walker, John G.; Phillips, Andrew J. (Institution of Engineering and Technology, 2014)
Wavelength division multiplexing (WDM) has been proposed for fibre, intersatellite, free space and indoor optical communication systems. Digital pulse position modulation (DPPM) is a more power efficient modulation format than on-off keying (OOK) and a strong contender for the modulation of free-space systems. Although DPPM obtains this advantage in exchange for a bandwidth expansion, WDM systems using it are still potentially attractive, particularly for moderate coding levels. However, WDM systems are susceptible to interchannel crosstalk and modelling this in a WDM DPPM system is necessary. Models of varying complexity, based on simplifying assumptions, are presented and evaluated for the case of a single crosstalk wavelength. For a single crosstalk, results can be straightforwardly obtained by artificially imposing the computationally convenient constraint that frames (and thus slots also) align. Multiple crosstalk effects are additionally investigated, for the most practically relevant cases of modest coding level, and using both simulation and analytical methods. In general, DPPM maintains its sensitivity advantage over OOK even in the presence of crosstalk while predicting lower power penalty at low coding level in WDM systems.